India in Abe Shinzo's foreign policy - Dobrinskaya O.A. (Ежегодник Япония, 2020)
The article covers new trends in the Japan-India relations. The rapprochement of the two states which began after the end of the Cold war was given impetus in the 2000s, especially evident during the tenure of Prime Minister Abe (2006–2007, 2012 — now). The aim of this article is to study the dynamism of the bilateral relations during the period of premiership of Shinzo Abe, and to analyze the factors which influence the process of the two countries getting closer to each other. The shift in Japan’s focus towards the Indian Ocean and the announcement of the Free and Open Indo Pacific Strategy is driven by the desire to contain growing China’s influence, and India is seen as one of Japan’s main partners. Under Abe the level of relations was upgraded to special strategic and global partnership, intensive dialogue is being carried out both on bilateral and trilateral levels (with the US and Australia), and the Quad cooperation is being discussed. Defense cooperation is gaining momentum, including military exchanges, drills, defense technology cooperation. Of special interest is the perspective of joint US, Japan, India defense cooperation in the Indian ocean. As an answer to the Chinese Belt and Road Initiative Japan is pushing its Quality Infrastructure Initiative which includes investing heavily in India’s infrastructure and cooperating with India in the third countries. New prospects for economic cooperation emerge which include new spheres such as atomic energy cooperation, space exploration, IT and startups. Complementarity of the economies of the two countries which is based on combining Japan’s technologies and Indian human resources is at the core of further cooperation. It can be said that the closer relations between Japan and India are part of their strategies aimed at the containment of China, and their bilateral relations reach the level of quasi-alliance. At the same time considering close trade, economic and political relations of both India and Japan with China and India’s policy of non-alignment it should be noted that there are factors limiting possible forms of cooperation and slowing down further rapprochement.